Review. Successful family language policy: Parents, children and educators in interaction, edited by Mila Schwartz and Anna Verschik - Francesca Walls (Bellaterra Journal of Teaching & Learning Language & Literature, 2015)
Demonstrating a burgeoning interest in the field of family language policy (FLP) around the world, Successful Family Language Policy comprises several contributions from researchers working on multiple different contexts, united in their aim to address the key question of what makes some families successful in achieving bi- or multilingual outcomes for their children and others not.  Many factors that might contribute towards or jeopardise success are put forward throughout the course of the volume, helping to lay the groundwork in outlining the broad scope of the question and its implications.  This is a valuable first step which, with further research and collaboration, should enable the establishment of a common theoretical framework and methodological approach that might fit the complex, multi-level phenomenon that is FLP and help provide nuanced answers for researchers and parents alike.